Early detection of pancreatic cancer: impact of high-resolution imaging methods and biomarkers - Frič, Přemysl; Škrha, Jan; Šedo, Aleksi; Zima, Tomaš; Bušek, Petr; Kmochová, Klára; Laclav, Martin; Bunganič, Bohuš; Solař, Svatopluk; Hrabal, Petr; Bělina, František; Záruba, Pavel; et al. (European journal of gastroenterology & hepatology, 2016)
High-resolution imaging methods (HRIMs) and biomarkers present the second step of pancreatic cancer (PC) diagnostics in at-risk individuals. These include patients with positive risk factors, early symptoms, nonresponders to the initial antidiabetic therapy, patients older than 50 years of age with new-onset unstable diabetes requiring insulin as well as patients with long-term insulin-non-dependent diabetes and recent (up to 6 months) failure of antidiabetic therapy. The procedures should be started without delay and the co-operation between the primary and tertiary medical centers is highly desirable. An early indication of HRIMs and biomarkers is a prerequisite for the diagnosis of a resectable PC. This publication reviews the recent contribution of HRIMs and biomarkers toward an early diagnosis of PC.
Keywords: multidetektorová počítačová tomografie; Early Detection of Cancer; Antibodies; protilátky; Carcinoma, Pancreatic Ductal; mikro RNA; Elasticity Imaging Techniques; Endosonography; Plectin; nádory slinivky břišní; adenom; endosonografie; Adenoma; MicroRNAs; duktální karcinom slinivky břišní; časná detekce nádoru; cholangiopankreatografie endoskopická retrográdní; elastografie; magnetická rezonanční tomografie; Cholangiopancreatography, Magnetic Resonance; Positron Emission Tomography Computed Tomography; Magnetic Resonance Imaging; ultrasonografie; Carcinoma in Situ; magnetická rezonanční cholangiopankreatografie; Neoplasms, Cystic, Mucinous, and Serous; Cholangiopancreatography, Endoscopic Retrograde; Humans; nádory cystické, mucinózní a serózní; biologické markery; PET/CT; Pancreatic Neoplasms; Ultrasonography; plektin; Biomarkers; Multidetector Computed Tomography; karcinom in situ; lidé